PALAEO-ECOLOGICAL SIGNIFICANCE OF PALAEOCENE CALCAREOUS ALGAE FROM THE CAUVERY BASIN, INDIA - Kishore, S. (Ecoprint: An International Journal of Ecology, 2004)
Palaeocene limestone of the Ninniyur Formation of the Cauvery Basin contains abundant well-preserved calcareous algae. These various types of calcareous algal seem to be controlled by the characteristics of each type environments in which they developed and thus they provide useful palaeo-ecological information of the Ninniyur Formation. The distribution patterns of these groups of calcareous algae, extending from tidal flat to reefal environments have been observed in the Palaeocene of the Ninniyur Formation, Cauvery Basin South India. Key words: Ninniyur formation, Calcareous algae, Palaeoecology. Ecoprint Vol.11(1) 2004.